Roy Adaptation Model: integrative review of studies conducted in the light of the theory - Lays Pinheiro de Medeiros; Mayara Beatriz da Costa Souza; Julliana Fernandes de Sena; Marjorie Dantas Medeiros Melo; Jéssika Wanessa Soares Costa; Isabelle Katherinne Fernandes Costa (Universidade Federal do Ceará, 2015)
Objective: to identify the scientific evidence about the components of the Roy Adaptation Model in the population studied in the light of this theory. Methods: this is an integrative literature review in databases of the Latin-American and Caribbean Center on Health Sciences Information, Medical Literature Analysis and Retrieval System Online, Spanish Bibliographic Index on Health Sciences, Nursing Database, PubMed Central, Cumulative Index to Nursing and Allied Health Literature, Web of Science, and SciVerse Scopus. The sample consists of 20 articles published between 2005 and 2013. Results: the three types of stimuli, 38 of 82 adaptive problems, the four adaptive modes, and the six steps of the nursing process were identified. Conclusion: there is need for further studies on this theory and that address the entire nursing process, culminating in the increase in specific nursing knowledge and affirmation of this science in health.